2017
DOI: 10.1038/s41598-017-01334-x
|View full text |Cite
|
Sign up to set email alerts
|

General description and understanding of the nonlinear dynamics of mode-locked fiber lasers

Abstract: As a type of nonlinear system with complexity, mode-locked fiber lasers are known for their complex behaviour. It is a challenging task to understand the fundamental physics behind such complex behaviour, and a unified description for the nonlinear behaviour and the systematic and quantitative analysis of the underlying mechanisms of these lasers have not been developed. Here, we present a complexity science-based theoretical framework for understanding the behaviour of mode-locked fiber lasers by going beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This means there is a fixed point in a phase space description. A simple model which leads to a nice geometrical interpretation of the laser dynamics, based solely on gain saturation and saturation of the nonlinear loss, has been proposed by Li et al [31], and later expanded by Wei et al [32]. From the model presented in [31] a picture similar to the logistic map is obtained and a period doubling route to chaos using pulse saturation energy as a control parameter is clearly demonstrated numerically.…”
Section: Resultsmentioning
confidence: 98%
“…This means there is a fixed point in a phase space description. A simple model which leads to a nice geometrical interpretation of the laser dynamics, based solely on gain saturation and saturation of the nonlinear loss, has been proposed by Li et al [31], and later expanded by Wei et al [32]. From the model presented in [31] a picture similar to the logistic map is obtained and a period doubling route to chaos using pulse saturation energy as a control parameter is clearly demonstrated numerically.…”
Section: Resultsmentioning
confidence: 98%
“…Note that if the PTF is curved, oscillates, and intersects with P in = P out line multiple time and there are more than one stable fixed points like the point B, the system is sensitive to initial conditions and is often characterized by instability and chaos [3], [46]. For our system, we obtained a stable intracavity pulse power at 2.8 kW, as shown in Fig.…”
Section: Design Principles and Stability Characteristicsmentioning
confidence: 99%
“…In addition to verifying the feasibility of the system, we have also studied its stability and summarized the design principles. We found that the open loop energy transfer function (ETF) or the peak power transfer function (PTF) [3], [45] was the most important tool in the design of this system. Indeed, the shape of the PTF (which is more sensitive than ETF) is the key factor governing system performance.…”
Section: Design Principles and Stability Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passively mode-locked fiber lasers based on nonlinear polarization rotation have been widely investigated because of their inherent advantages and attractive properties. Due to the comprehensive interplay among many factors (nonlinear, dispersion, gain and loss), pulses risen in a mode-locked fiber laser usually have rich and complex nonlinear dynamics [1]. Various pulse states [2][3][4], such as Q-switched pulse, conservative soliton, stretched pulse, dissipative soliton, noise-like pulse, and similariton, have been reported depending on cavity configuration.…”
Section: Introductionmentioning
confidence: 99%